Board Involvement on Earnings Per Share (Eps): Evidence from A Developing Economy - DHARMADASA, P.; RATHNASINGHA, D. L. M.; CHRISTIAN, N.T.; PRADEEP, M. P. (My University, 2018)
This research aims to investigate the effect of board involvement on earnings per share. The current study uses the correlation and regression models to analyze publicly available data for a sample of 69 firms quoted in the Nigerian Stock Exchange for the fiscal year 2011. This indicates that the research made use of cross sectional data. Several diagnostic tests have been applied to justify the validity of the results. The empirical investigations reveal that director’ shareholdings, board size and board skills have significant impact on performance. Good corporate governance standards are very essential to every organization and should be encouraged and practiced for the interest of the investors, shareholders and other stakeholders. Is worthy of note, that from a developing country like Nigeria, especially in sub-Saharan Africa, this paper is the first of its kind and offers evidence on the effect of board involvement on earnings per share. The paper provides useful information that is of great value to policy makers, academia, corporate firms and other stakeholders.
Keywords: Board Involvement; Firm Performance; Earnings per Share